Sipunculus nudus genome provides insights into evolution of spiralian phyla and development - Qi, Yi; Chen, Liang; Wu, Binhua; Tang, Xiaoning; Zhu, Xiao; Li, Ru; Wu, Kefeng; Luo, Hui (Frontiers in Marine Science, 2023)
Introduction Sipunculus nudus is the most known species in the genus Sipunculus, distributed in tropical and subtropical coastal waters. Methods PacBio sequencing and Illumina sequencing were combined for whole-genome sequencing of S. nudus. LC-MS/MS analysis was performed for the metabolomics of S. nudus. Results Herein, we report a 1.75 Gb complete genome assembly with a contig N50 size of 450 kb of the S. nudus based on a strategy combining third-generation long-read sequencing and Illumina sequencing. A total of 80391 protein-coding genes are annotated in this genome. Furthermore, gene family evolution analysis shows that S. nudus belonged to Mollusca or was close to Mollusca, but distinct with Annelida. Transcriptome analysis indicates the involvement of complex developmental events in larve. KEGG pathway analysis of differentially expressed genes showed that these DEGs were mainly enriched in the pathway of amino acid metabolism, lipid metabolism and transport and catabolism. LC-MS/MS analysis shows that S. nudus was rich in a variety of nutritional and functional components, such as carnitine, free amino acids, unsaturated fatty acids, inosine and methionine sulfoxide. Combined transcriptome with LC-MS/MS analysis, the results showed that gene expression and metabolic level involved in the inosine, arginine and proline biosynthesis of S. nudus during different growth stages were significantly changed. Discussion Our genome assembly provides an important genome resource and new insight into the relationships of Sipuncula to other spiralian phyla. Meanwhile, transcriptome and LC-MS/MS analysis reveal the systematic gene expression profiles and metabolite components of S. nudus during different growth stages, which provide new insight into the exploration and development of bioactive molecules of S. nudus.